(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2022)
Some people in Mojokerto use pineapple crowns as medicine to remove a kidney stones. However, research related to this topic is very limited, there is no specific data regarding the content of active substances in pineapple crown. So that in this study, kidney stone decay was tested with pineapple crown extract and analyzed the phytochemicals of pineapple crown were. The effect on the ability of pineapple crown to remove kidney stones was carried out in vitro by testing kidney stones obtained from one of the patients with kidney stone disease. The solubility of calcium oxalate which is the content of kidney stones was tested against pineapple crown extract with various solvents. While the phytochemical test was carried out 6 times on the extraction of pineapple crown with various solvent variations. From the results of tests carried out on the content of several phytochemical compounds such as saponins, tannins, flavonoids, triterpenoids, and steroids, it was found that the highest content was found in pineapple crown extract with water and ethanol solvents. From the in vitro test results of kidney stone solubility, it was found that there was an effect of pineapple crown on kidney stone solubility although it was not significant. The optimum concentration of pineapple crown extract from several variations of the concentration tested was 0.0625 M. Through this research, can provide scientific facts to the public about the use of pineapple crown extract for kidney stone removal.